Communications Technology and Terrorism - Rafat Mahmood; Michael Jetter (Center for Economic Studies and ifo Institute (CESifo), 2018)
By facilitating the flow of information in society, communications technology (CT; e.g., newspapers, radio, television, the internet) can help terrorists to (i) spread their message, (ii) recruit followers, and (iii) coordinate among group members. However, CT also facilitates monitoring and arresting terrorists. This paper formulates the hypothesis that a society's level of CT is systematically related to terrorism. We introduce a simple theoretical framework, suggesting that terrorism first becomes more attractive with a rise in CT, but then decreases, following an inverted U-shape. Accessing data for 199 countries from 1970-2014, we find evidence for these predictions: Terrorism peaks at intermediate ranges of CT and corresponding magnitudes are sizeable. Our estimations control for a range of potentially confounding factors, as well as country- and year-fixed effects. Results are consistent throughout a battery of robustness checks and placebo regressions. Finally, we find no evidence of a potential reporting bias explaining our findings.
Keywords: D74; D83; L82; L86; L96; P16; 330; communications technology; GTD; information flows; terrorism; panel data